Assessment of spatial variability and temporal dynamics of Dissolved Organic Matter (DOM) at lower Kinabatangan River Catchment, Sabah. - Norizati Murdin; Chong, Harry Lye Hin; Salani Selveno; Sahana Harun; Arman Hadi Fikri (Universiti Malaysia Sabah, 2019)
The spatial and temporal variability of dissolved organic matter (DOM) characteristics and surface water quality in the Lower Kinabatangan River Catchment were determined between October 2015 and May 2016. The objectives of this study were: (i) to distinguish the DOM absorption characteristics and physicochemical quality of surface water draining from different types of land use: oil palm plantation (OP), secondary forest (SF) and semi-natural vegetation (SV); and to examine its temporal variations during dry and wet periods. The collected physicochemical parameters data was analysed and classified based on the Malaysian National Water Quality Standard (NWQS). Findings indicated all the parameters fall into Class I, except for pH, total suspended solids (TSS) and concentration dissolved oxygen (DO). Linear discriminant analysis has been applied to distinguished the physico-chemical and absorption DOM properties data into mutually-exclusive spatial and temporal groups. Interestingly, the pH, DO and total nitrogen values were exhibited as dominant parameters at SV during both low and high rainfall periods. The dominance of these parameters suggested that the spatially and temporally varied water quality were influenced by both natural processes (e.g precipitation rate) and anthropogenic factor (e.g land use change). Whereas, both absorption coefficients (a340) and spectral slope (S275-295) were more dominant at SF and OP respectively. This might be due to increasing terrestrial DOM loadings as well as significant degradation of DOM via microbial and/or photochemical reaction.